Professor Dr. Jiri Sehnal - A Life for the History of Music in Moravia - Riedel, Wilhelm Friedrich (Musicologica Olomucensia, 2011)
The importance of the organizational and scholarly work of Jiri Sehnal can be found in the following areas:I. Rescue, centralization, preservation and cataloging of musical sources of the leading collections of Moravian monasteries, churches.II. Numerous publications and surveys, which Sehnal presented during more than thirty years at conferences and published, extraordinarily he contributed to the international awareness of the important history of music in Moravia.III. Research and display of technical, economic, architectural and acoustic organ development in Moravia.
Keywords: Conservation; musical sources; publications; history of music; organ